Giant vesical calculus with carcinoma bladder: A rare entity - Batra, R; Agarwal, AA; Sharma, P; Pradeep, B; Gupta, D (Journal of College of Medical Sciences-Nepal, 2012)
A 60 year old male attended with history of dribbling of urine for one year along with frequent passing of urine at night for last 15-20 days. Rectal examination showed suggesting of 2 grad prostrate enlargement. Ultrasound shows vesicle calculus with no prostrate enlargement. At cystolithotomy, calculus (10x8x5cm) was noted. Histopathology shows keratinising squamous cell carcinoma. Postoperatively radiotherapy was done. Vesico cutaneous fistula was developed that healed subsequently. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 61-63 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6730